2018
DOI: 10.1093/gerona/gly177
|View full text |Cite
|
Sign up to set email alerts
|

Disadvantaged Early-Life Socioeconomic Circumstances Are Associated With Low Respiratory Function in Older Age

Abstract: Abstract Background Poor lung function in late life may stem from early-life risk factors, but the epidemiological evidence is inconsistent. We investigated whether individuals who experienced disadvantageous socioeconomic circumstances (SEC) in early life showed lower levels of respiratory function in older age, a steeper decline over time, and whether these relationships were explained by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 40 publications
3
16
0
Order By: Relevance
“…These four binary indicators served to create an index of childhood socioeconomic circumstances with five categories ranging from “most disadvantaged” to “most advantaged”. Disadvantaged CSC have been shown to predict a wide range of health indicators, including muscle strength (Cheval, Boisgontier, et al, 2018), lung function (Cheval, Chabert, et al, 2018), frailty (van der Linden et al, 2017), disability (Landös et al, 2018), and physical inactivity (Cheval, Sieber, et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…These four binary indicators served to create an index of childhood socioeconomic circumstances with five categories ranging from “most disadvantaged” to “most advantaged”. Disadvantaged CSC have been shown to predict a wide range of health indicators, including muscle strength (Cheval, Boisgontier, et al, 2018), lung function (Cheval, Chabert, et al, 2018), frailty (van der Linden et al, 2017), disability (Landös et al, 2018), and physical inactivity (Cheval, Sieber, et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…The results of this study highlighted the signi cance of early life conditions in the low and middle-income setting. Poor socioeconomic status across the life course continues to affect the individual outcomes on various health measures such as handgrip strength (69), frailty (70), and respiratory function (71). Studies showed that childhood socioeconomic status plays an important role in access to nutrition, health, and education which further affect the various individual outcomes throughout the life course (24,47).…”
Section: Discussionmentioning
confidence: 99%
“…This research was not designed to evaluate the causal mechanism of this association. Other research, however, points to the potential complexity of the associations between pulmonary and cognitive health (35)(36)(37)(38)(39) and future longitudinal research could investigate directional and common causal mechanisms (eg, Does cognitive deterioration lead to physical decline? Do small pulmonary changes lead to cognitive decline?…”
Section: Discussionmentioning
confidence: 99%